Same, same but different: A comparative study of the Swedish and German support systems for young victims of crime - Thunberg, Sara (European journal of criminology, 2022)
Sweden and Germany are often compared, which suggests that much can be learned from each country. One aspect that needs further investigation concerns support for young victims of crime. The study therefore compares the Swedish and German welfare systems? handling of young victims who need support after victimization, to see what can be learned from each respective country. The comparisons make it clear that both countries? support systems developed out of similar social movements in the 1970s. However, there are differences between the two welfare states? approaches to supporting young people. The reasons for the similarities and differences are discussed, along with practical implications for social policy.